Discourses on War and Peace in a Professional Ethics Classroom - V.K. Karthika (Radical Teacher, 2023)
Empty seats, uninterested faces and distracted student behaviour are general characteristics of the classroom where humanities subjects are taught to students of science and technology. In this article, I discuss my experience of teaching a course, Professional Ethics, that is generally discarded by the students as ‘an additional burden’ made mandatory by the All India Council for Technical Education (AICTE) for securing a bachelor of technology degree from Indian institutes of higher education. The teaching note documents the initial attitude of students towards the course content, the process of their transformation into imbibing the essence of the course, and finally the outcomes of the adapted teaching method. Socratic questioning on memes and news reports was used to sensitise the students towards the ethics of war and weapon development. In other words, the teaching process was a discourse of peace building by engaging students in sustainability dialogues.